2022
DOI: 10.2196/36806
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Therapist Expectations for a Blended Cognitive Behavioral Therapy Program for Depression: Qualitative Exploratory Study

Abstract: Background Blended cognitive behavioral therapy (bCBT)—the combination of digital elements and face-to-face psychotherapy—has been proposed to alleviate challenges that patients and therapists face in conventional cognitive behavioral therapy. There is growing evidence that adding digital elements to face-to-face psychotherapy can contribute to better treatment outcomes. However, bCBT programs still show considerable shortcomings, and knowledge on how to improve digital apps using a bCBT protocol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Interestingly, our study showed that the perceived benefits of this bCBT program are in line with many of the explored expectations of patients receiving standard CBT but who have not yet had an experience with blended formats [ 38 , 49 ]. This study confirms that inexperienced bCBT users’ needs for personalization, integration into daily life, psychoeducation, and self-reflection options match the experiences of participants in this bCBT program.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Interestingly, our study showed that the perceived benefits of this bCBT program are in line with many of the explored expectations of patients receiving standard CBT but who have not yet had an experience with blended formats [ 38 , 49 ]. This study confirms that inexperienced bCBT users’ needs for personalization, integration into daily life, psychoeducation, and self-reflection options match the experiences of participants in this bCBT program.…”
Section: Discussionsupporting
confidence: 54%
“…This study confirms that inexperienced bCBT users’ needs for personalization, integration into daily life, psychoeducation, and self-reflection options match the experiences of participants in this bCBT program. However, participants also called for more interactive therapeutic activities, which patients inexperienced in bCBT did not mention as a preference [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations